Endoscopic Endonasal Resection of Tuberculum Sellae Meningioma with Utilization of Indocyanine Green - Shahein, Mostafa; Montaser, Alaa S.; Todeschini, Alexandre B.; Revuelta Barbero, Juan M.; Otto, Bradley A.; Carrau, Ricardo L.; Prevedello, Daniel M. (Journal of Neurological Surgery Part B: Skull Base, 2018)
We present the case of a 67-year-old female with an incidental finding of a left-sided tuberculum sellae meningioma on a brain magnetic resonance imaging (MRI) for an unrelated complaint. Formal visual field testing showed a small defect in the inferior nasal and temporal fields of the left eye, compatible with mass effect on the optic nerve by the tumor.An endoscopic endonasal transtuberculum approach with decompression of the left optic nerve was performed using a standard binostril four-hand technique, with the patient positioned supine with the head turned to the right side and tilted to the left, fixed in a three-pin head clamp, under imaging guidance. After exposure, we drilled the tuberculum sellae and the floor of the sella and after opening the dura, the tumor and optic nerve came into view. The tumor was completely removed and we confirmed the patency of all perforating vessels using indocyanine green. Reconstruction was done in a multilayered fashion, using collagen matrix and a nasoseptal flap.Patient had an uneventful postoperative stay and was discharged on postoperative day 3, neurologically stable with no new hormonal deficits. Pathology report confirmed a WHO Grade I meningioma with Ki-67 of 1% and 3-month postoperative MRI confirmed a gross total resection and visual fields exam showed a complete recovery.The link to the video can be found at: https://youtu.be/zRmt2aIvX5c.
Keywords: endoscopic endonasal; tuberculum sellae meningioma; indocyanine green; ICG